Anti-Utopian Outlook in The Every by Dave Eggers - Galina I. Lushnikova; Tatiana Iu. Osadchaia (СибСкрипт)
The Every (2021) is an anti-utopian novel by a contemporary American writer Dave Eggers. The study relied on domestic and foreign research on the issues of artistic worldview, as well as on the genres of utopia, antiutopia, and dystopia. Modern anti-utopian fiction still remains understudied from the artistic outlook perspective. The research objective was to determine the key features of the anti-utopian worldview and analyze how they were implemented in the novel. Eggers’ world of the future is a possible world implemented through the system of images and ideas. It differs from other anti-utopian worlds because it combines anti-utopian and realistic features. In addition, both the future and the present are subjected to satire, which is combined with irony, absurdity, and paradox. The Every develops the theme of totalitarian power of an omnipotent corporation and its consequences. The chronotope is unlimited; the main character is a rebel, an active opponent of the authorities. The author’s modality is a straightforward criticism of the fictional reality.